Sterilizable porous filtration media containing nanofiber
Patent Information
- Application Number
- JP2024119307
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2020-02-18
- Filing Date
- 2024-07-25
- Publication Date
- 2026-10-16
AI Technical Summary
Current nanofiber-based liquid filtration membranes in the biopharmaceutical industry are susceptible to structural changes and performance degradation due to wetting and drying processes, including steam sterilization, leading to reduced water permeability and integrity loss.
Development of porous, nonwoven polymeric nanofiber mats that undergo heat treatment at or below the glass transition temperature but below the melting temperature, ensuring thermal equilibrium without temperature ramp-up or cool-down, making them compatible with moist heat sterilization processes.
The treated nanofiber mats maintain high permeability and retention capabilities after multiple sterilization cycles, with minimal changes in liquid permeability, bubble point, and log reduction value, ensuring robust performance in critical filtration applications.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit of priority to U.S. Provisional Patent Application No. 62 / 977,884, filed February 18, 2020, the entire contents of which are incorporated herein by reference. [Background technology]
[0002] Most filtration applications in the biopharmaceutical industry require a sterilization step performed by the drug manufacturer or a pre-sterilization step performed by the filter manufacturer. The sterilization step may include, for example, either steam-in-place or autoclave sterilization. These sterilization methods exert either high temperature or high energy on the membrane and filtration device. In addition, most devices sold for critical filtration applications are 100% integrity tested, meaning that every device sold is tested at least once. Most such integrity tests require wetting of the filtration media inside the device, followed by testing and drying. To perform well in these critical filtration applications, the membrane structure needs to withstand these harsh conditions. Unfortunately, for current nanofiber-based liquid filtration membranes, the stability and performance of the membrane structure are negatively affected by wetting / drying cycles, both with heating (e.g., autoclaving) and without heating (e.g., integrity testing). Summary of the Invention
[0003] Provided herein are methods and compositions relating to nanofiber structures (e.g., nanofiber mats) that exhibit high permeability and retention after any wet-dry process, including moist heat sterilization (e.g., autoclaving, steam-in-place sterilization, and / or tyndallization).
[0004] In some embodiments, a method of making a porous, nonwoven, polymeric nanofiber-containing liquid filtration medium compatible with moist heat sterilization includes filtration of the porous, nonwoven, nanofiber-containing liquid medium at a temperature above at least the glass transition temperature (T g ), but the melting temperature (T m ) or less for at least the time necessary to achieve thermal equilibrium with the heating medium, not including a temperature ramp-up and cool-down.
[0005] In some embodiments, the polymer nanofibers are compatible with moist heat sterilization and have a glass transition temperature (T g ), but the melting temperature (T m Provided herein is a liquid filtration medium comprising a porous polymeric nanofiber mat heated to a temperature below 100° C. for a period of time required for thermal equilibration, not including temperature ramp-up and cool-down.
[0006] In certain embodiments, a method of sterilizing a porous, nonwoven, polymeric nanofiber-containing liquid filtration medium is provided, comprising sterilizing the liquid filtration medium at a temperature of at least the glass transition temperature (T g ), but the melting temperature (T m ) for at least one hour and sterilizing the heat-treated liquid filtration medium using moist heat sterilization.
[0007] In a further aspect, a method for removing bacteria from a liquid sample is provided, comprising: filtering a porous, nonwoven, polymeric nanofiber-containing liquid filtration medium at a temperature above at least the glass transition temperature (T g ), but the melting temperature (T m ) for at least one hour, sterilizing the liquid filtration medium using moist heat sterilization, and passing the bacteria-containing liquid sample through the sterilized liquid filtration medium.
[0008] Certain embodiments provided herein include a method for removing viral particles from a liquid sample, the method comprising: filtering a porous, nonwoven, polymeric nanofiber-containing liquid filtration medium at a temperature above at least the glass transition temperature (T g ), but the melting temperature (T m ) or less for at least the time necessary to reach thermal equilibrium, sterilizing the liquid filtration medium using moist heat sterilization, and passing the liquid sample containing the viral particles through the sterilized liquid filtration medium.
[0009] Thus, in certain aspects, there is provided herein an autoclavable porous nonwoven nanofiber liquid filtration medium prepared according to the methods disclosed herein, and a critical mass filtration device comprising such liquid filtration medium for use in critical mass filtration applications. In certain embodiments, such liquid filtration medium is particularly used in sterile filtration (aseptic) applications.
[0010] In one aspect, the present invention provides a method for producing a porous, nonwoven, polymeric nanofiber-containing liquid filtration medium that is compatible with any wetting and drying process, such as integrity testing or moist heat sterilization, comprising: filtering the porous, nonwoven, nanofiber-containing liquid filtration medium at a temperature above at least the glass transition temperature (T g ), but the melting temperature (T m ) or less for at least 1 hour.
[0011] In another aspect of the invention, a liquid filtration medium is made by electrospinning a polymer solution or melt to produce a porous, non-woven polymeric nanofiber mat.
[0012] In another aspect of the invention, the liquid filtration medium is heated to at least the glass transition temperature (T g ), but the melting temperature (T m ) to resist changes in liquid permeability after sterilization relative to corresponding filtration media that have not been heated to or below 100°C.
[0013] In another embodiment of the invention, the liquid filtration media exhibits a bubble point pressure of between 5 psi and 150 psi (psig).
[0014] In another embodiment of the invention, the liquid filtration medium exhibits a bubble point of 15 psi or greater.
[0015] In another embodiment of the invention, the liquid filtration medium is subjected to at least T of the polymeric nanofibers for at least 1 hour. g However, T m There is less change in bubble point after sterilization compared to the same liquid filtration media that has not been heated to
[0016] In another embodiment of the invention, the bubble point is measured using Galwick® as the wetting fluid.
[0017] In another embodiment of the present invention, the liquid filtration medium exhibits a Brevundimonas diminuta log reduction value (LRV) of at least 1, measured according to ASTM F838-83.
[0018] In another embodiment of the invention, the liquid filtration medium exhibits a log reduction value (LRV) of at least 4, or at least 8, against Brevizimonas diminuta, as measured according to ASTM F838-83.
[0019] In another embodiment of the invention, the liquid filtration medium has a porosity of about 80% to about 95%.
[0020] In another embodiment of the present invention, the liquid filtration media exhibits a liquid permeability of greater than about 1000 LMH / psi.
[0021] In another embodiment of the present invention, the liquid filtration media exhibits a liquid permeability of greater than about 100 LMH / psi.
[0022] In another embodiment of the present invention, the liquid filtration media exhibits a liquid permeability of greater than about 10 LMH / psi.
[0023] In another embodiment of the invention, the liquid filtration medium is subjected to at least T of the polymeric nanofibers for at least 1 hour. g However, T m The filtration media exhibits higher liquid permeability after sterilization compared to the same filtration media that has not been heated.
[0024] In another embodiment of the invention, the liquid filtration media exhibits no more than a 40% decrease in liquid permeability after sterilization.
[0025] In another embodiment of the invention, the liquid filtration media exhibits no more than a 30% decrease in liquid permeability after sterilization.
[0026] In another embodiment of the invention, the liquid filtration media exhibits no more than a 15% decrease in liquid permeability after sterilization.
[0027] In another embodiment of the invention, the nanofibers have a fiber diameter of about 5 nm to about 1000 nm.
[0028] In another embodiment of the invention, the liquid filtration media comprises 1) a symmetric nanofiber mat, or 2) an asymmetric nanofiber mat that exhibits fiber diameters that vary across the thickness of the nanofiber mat, such that the average fiber diameter in one layer of the nanofiber mat is different from that of another layer of the nanofiber mat.
[0029] In another embodiment of the invention, the average fiber diameter changes continuously from one layer of the asymmetric nanofiber mat to another layer.
[0030] In another embodiment of the invention, the ratio of average fiber diameter of one layer of the asymmetric nanofiber mat to another layer is at least 1.15.
[0031] In another embodiment of the invention, the average fiber diameter is from about 5 nm to about 1000 nm for at least one layer of the asymmetric nanofiber mat.
[0032] In another embodiment of the invention, the average fiber diameter is from about 5 nm to about 150 nm for at least one layer of the asymmetric nanofiber mat.
[0033] In another embodiment of the invention, the average fiber diameter is about 100 nm for at least one layer of the nanofiber mat.
[0034] In another embodiment of the invention, the average fiber diameter is about 5 nm for at least one layer of the nanofiber mat.
[0035] In another aspect of the invention, the polymer is selected from thermoplastic polymers, thermoset polymers, nylons, polyimides, aliphatic polyamides, aromatic polyamides, polysulfones, cellulose acetate, polyethersulfones, polyurethanes, poly(urea urethanes), polybenzimidazoles, polyetherimides, polyacrylonitriles, poly(ethylene terephthalate), polypropylene, polyaniline, poly(ethylene oxide), poly(ethylene naphthalate), poly(butylene terephthalate), styrene butadiene rubber, polystyrene, poly(vinyl chloride), poly(vinyl alcohol), poly(vinyl alcohol), poly(vinylidene fluoride), poly(vinyl butylene), and copolymers, derivative compounds or blends thereof.
[0036] In another embodiment of the invention, the polymer is an aliphatic polyamide.
[0037] In another embodiment of the invention, the polymer is selected from nylon-6, nylon-6,6, nylon 6,6-6,10, nylon-6 copolymer, nylon-6,6 copolymer, nylon 6,6-6,10 copolymer, and any mixtures thereof.
[0038] In another embodiment of the invention, the polymer is nylon-6,6.
[0039] In another embodiment of the invention, the method further comprises: mThis includes heating the mixture to about 1°C to about 80°C below the temperature.
[0040] In another embodiment of the invention, the method further comprises: m The method includes heating the mixture to about 56°C below room temperature.
[0041] In another embodiment of the invention, the method further comprises: m The method includes heating the mixture to about 75° C.
[0042] In another embodiment of the invention, the method further comprises: g This includes heating the mixture to about 100°C to about 200°C above the temperature.
[0043] In another embodiment of the invention, the method further comprises: g This includes heating the mixture to about 140°C to about 158°C above the desired temperature.
[0044] In another embodiment of the invention, the method includes heating the nanofiber mat to about 190°C to about 208°C.
[0045] In another embodiment of the invention, the method includes heating the nanofiber mat to about 208°C.
[0046] In another aspect of the invention, the method includes heating the nanofiber mat in a non-oxidizing environment, such as an inert atmosphere oven.
[0047] In another embodiment of the invention, the method includes heating the nanofiber mat for at least about 1 hour to at least about 24 hours.
[0048] In another embodiment of the invention, the method includes heating the filtration medium for at least about 12 hours.
[0049] In another aspect of the invention, the method includes any wet and dry process such as integrity testing, moist heat sterilization includes autoclaving, steam-in-place sterilization, and / or tindalization.
[0050] In another aspect of the invention, a porous, nonwoven, nanofiber-containing liquid filtration medium is electrospun onto the surface of a porous or non-porous support.
[0051] In another embodiment of the invention, the nanofiber mat is electrospun onto a surface of a porous or non-porous support, wherein the root mean square height of the surface of the porous, non-woven support is less than about 70 μm.
[0052] In another embodiment of the invention, the support comprises one or more layers produced by melt-blowing, wet-laying, spin-bonding, calendaring, electrospinning, electro-blowing, or any combination thereof.
[0053] In another aspect of the invention, the support comprises a thermoplastic polymer, a polyolefin, a polypropylene, a polyester, a polyamide, a copolymer, a polymer blend, a cellulosic, and combinations thereof.
[0054] In another embodiment of the invention, the closest pore size of the nanofiber layer is smaller than the closest pore size of the porous nonwoven support.
[0055] In another embodiment of the invention, the porous support comprises one or more layers selected from the group consisting of spunbonded nonwovens, meltblown nonwovens, needle punched nonwovens, spunlaced nonwovens, wet laid nonwovens, resin bonded nonwovens, electrospun nonwovens, electroblown nonwovens, woven fabrics, knitted fabrics, paper, and combinations thereof.
[0056] In another aspect, the invention relates to autoclavable porous, nonwoven nanofibrous liquid filtration media prepared according to the methods of the invention.
[0057] In one aspect, the present invention provides a method for preparing nanofibers that are compatible with any wetting and drying process, such as integrity testing or moist heat sterilization, and that can be used to maintain the nanofiber at least at the glass transition temperature (T g ), but the melting temperature (T m ) or less.
[0058] In another aspect of the invention, a liquid filtration medium is made by electrospinning a polymer solution or melt to produce a porous, non-woven polymeric nanofiber mat.
[0059] In another embodiment of the invention, the liquid filtration medium is subjected to at least T of the polymeric nanofibers for at least 1 hour. g However, T m The nanofiber mats are more resistant to changes in liquid permeability following sterilization compared to corresponding filtration media comprising nanofiber mats that have not been heated to
[0060] In another embodiment of the invention, the liquid filtration medium exhibits a bubble point pressure of between 5 psi and 150 psi.
[0061] In another embodiment of the invention, the liquid filtration medium exhibits a bubble point of 15 psi or greater.
[0062] In another embodiment of the invention, the liquid filtration medium is subjected to at least T of the polymeric nanofibers for at least 1 hour. g However, T m There is less change in bubble point after sterilization compared to the same liquid filtration media containing a nanofiber mat that has not been heated to .
[0063] In another embodiment of the invention, the bubble point is measured using Galwick® as the wetting fluid.
[0064] In another embodiment of the present invention, the liquid filtration medium exhibits a log reduction value (LRV) of at least 1 for Brevizimonas diminuta, measured according to ASTM F838-83.
[0065] In another embodiment of the present invention, the liquid filtration medium exhibits a log reduction value (LRV) of at least 4 for Brevizimonas diminuta as measured according to ASTM F838-83.
[0066] In another embodiment of the present invention, the liquid filtration medium exhibits a log reduction value (LRV) of at least 8 for Brevizimonas diminuta as measured according to ASTM F838-83.
[0067] In another embodiment of the invention, the liquid filtration medium has a porosity of about 80% to about 95%.
[0068] In another embodiment of the invention, the liquid filtration media exhibits a liquid permeability of greater than about 1000 LMH / psi after moist heat sterilization.
[0069] In another embodiment of the invention, the liquid filtration media exhibits a liquid permeability of greater than about 100 LMH / psi after moist heat sterilization.
[0070] In another embodiment of the invention, the liquid filtration media exhibits a liquid permeability of greater than about 10 LMH / psi after moist heat sterilization.
[0071] In another embodiment of the invention, the liquid filtration medium is subjected to at least T of the polymeric nanofibers for at least 1 hour. g However, T m The nanofiber mats exhibit higher liquid permeability after sterilization compared to corresponding liquid filtration media containing nanofiber mats that have not been heated.
[0072] In another embodiment of the invention, the liquid filtration media exhibits no more than a 40% decrease in liquid permeability after moist heat sterilization.
[0073] In another embodiment of the invention, the liquid filtration media exhibits no more than a 30% decrease in liquid permeability after moist heat sterilization.
[0074] In another embodiment of the invention, the liquid filtration media exhibits no more than a 15% decrease in liquid permeability after moist heat sterilization.
[0075] In another aspect of the invention, the liquid filtration media does not exhibit significant change in liquid permeability following moist heat sterilization.
[0076] In another embodiment of the liquid filtration medium, the nanofiber mat of the liquid filtration medium has a fiber diameter of about 5 nm to about 1000 nm.
[0077] In another embodiment of the liquid filtration medium, the liquid filtration medium comprises 1) an asymmetric nanofiber mat or 2) an asymmetric nanofiber mat that exhibits fiber diameters that vary across the thickness of the nanofiber mat, such that the average fiber diameter of one layer of the nanofiber mat is different than that of another layer of the nanofiber mat.
[0078] In another embodiment of the liquid filtration media, the average fiber diameter varies continuously from one layer of the nanofiber mat to another layer.
[0079] In another embodiment of the liquid filtration media, the ratio of average fiber diameter of one layer of the nanofiber mat to another layer is at least 1.15.
[0080] In another embodiment of the liquid filtration media, the average fiber diameter is from about 5 nm to about 1000 nm for at least one layer of the nanofiber mat.
[0081] In another embodiment of the liquid filtration media, the average fiber diameter is from about 5 nm to about 100 nm for at least one layer of the nanofiber mat.
[0082] In another embodiment of the liquid filtration media, the average fiber diameter is about 100 nm for at least one layer of the nanofiber mat.
[0083] In another embodiment of the liquid filtration media, the average fiber diameter is about 5 nm for at least one layer of the nanofiber mat.
[0084] In another aspect of the liquid filtration medium, the polymer is selected from thermoplastic polymers, thermoset polymers, nylon, polyimides, aliphatic polyamides, aromatic polyamides, polysulfones, cellulose acetate, polyethersulfones, polyurethanes, poly(urea urethanes), polybenzimidazoles, polyetherimides, polyacrylonitrile, poly(ethylene terephthalate), polypropylene, polyaniline, poly(ethylene oxide), poly(ethylene naphthalate), poly(butylene terephthalate), styrene butadiene rubber, polystyrene, poly(vinyl chloride), poly(vinyl alcohol), poly(vinylidene fluoride), poly(vinyl butylene), and copolymers, derivative compounds, or blends thereof.
[0085] In another embodiment of the liquid filtration media, the polymer is an aliphatic polyamide.
[0086] In another embodiment of the liquid filtration medium, the polymer is selected from nylon-6, nylon-6,6, nylon 6,6-6,10, nylon-6 copolymers, nylon-6,6 copolymers, nylon 6,6-6,10 copolymers, and any mixtures thereof.
[0087] In another embodiment of the liquid filtration medium, the polymer is nylon-6,6.
[0088] In another embodiment, the nanofiber mat is m The mixture was heated to about 1°C to about 80°C below the temperature.
[0089] In another embodiment of the liquid filtration media of the present invention, the nanofiber mat is m The mixture was heated to about 56°C below room temperature.
[0090] In another embodiment of the liquid filtration media of the present invention, the nanofiber mat is mThe mixture was heated to about 75°C below room temperature.
[0091] In another embodiment of the liquid filtration media of the present invention, the nanofiber mat is g The mixture was heated to about 100°C to about 200°C.
[0092] In another embodiment of the liquid filtration media of the present invention, the nanofiber mat is g The mixture was heated to about 140°C to about 158°C.
[0093] In another embodiment of the liquid filtration media of the present invention, the nanofiber mat was heated to about 190°C to about 208°C.
[0094] In another embodiment of the liquid filtration media of the present invention, the nanofiber mat was heated to about 208°C.
[0095] In another embodiment of the liquid filtration media of the present invention, the nanofiber mat was heated in a non-oxidizing environment, such as an inert atmosphere oven.
[0096] In another embodiment of the liquid filtration media of the present invention, the nanofiber mat is heated for at least about 1 hour to at least about 24 hours.
[0097] In another embodiment of the liquid filtration media of the present invention, the nanofiber mat is heated for at least about 12 hours.
[0098] In another embodiment of the liquid filtration media of the present invention, integrity testing, moist and dry processes such as moist heat sterilization include autoclaving, steam-in-place sterilization, and / or tindalization.
[0099] In another embodiment of the liquid filtration media of the present invention, a porous, nonwoven, nanofiber-containing liquid filtration media is electrospun onto the surface of a porous or non-porous support.
[0100] In another embodiment of the liquid filtration media of the present invention, the nanofiber mat is electrospun onto a surface of a porous or non-porous support, and the root mean square height of the surface of the porous, non-woven support is less than about 70 μm.
[0101] In another embodiment of the liquid filtration media of the present invention, the support comprises one or more layers produced by meltblowing, wet laying, spin bonding, calendaring, electrospinning, electroblowing, or any combination thereof.
[0102] In another aspect of the liquid filtration media of the present invention, the support comprises a thermoplastic polymer, a polyolefin, a polypropylene, a polyester, a polyamide, a copolymer, a polymer blend, a cellulosic, and combinations thereof.
[0103] In another embodiment of the liquid filtration media of the present invention, the closest pore size of the nanofiber layer is smaller than the closest pore size of the porous nonwoven support.
[0104] In another embodiment of the liquid filtration medium of the present invention, the porous support comprises one or more layers selected from the group consisting of spunbonded nonwovens, meltblown nonwovens, needlepunched nonwovens, spunlaced nonwovens, wetlaid nonwovens, resinbonded nonwovens, electrospun nonwovens, electroblown nonwovens, woven fabrics, knitted fabrics, paper, and combinations thereof.
[0105] In another aspect, the invention comprises an autoclavable porous, nonwoven nanofiber liquid filtration medium prepared according to the methods of the invention.
[0106] In another aspect, the present invention includes a filtration device for use in critical temperature filtration comprising one or more layers of the porous composite media of the present invention.
[0107] In one aspect, the invention comprises a porous asymmetric flat membrane prefilter having a dense layer and a porous layer with increasing size between the dense layer and the porous layer, and a retentive layer comprising the liquid filtration medium of any one of claims 48 to 97 located on the dense layer of the porous asymmetric flat membrane, wherein the pore size of the retentive layer is smaller than the pore size of the dense layer of the porous asymmetric flat membrane prefilter.
[0108] In another embodiment, the porous composite medium has a bubble point, measured in a liquid, that is at least 20% greater than the bubble point of the porous flat sheet membrane prefilter alone.
[0109] In another embodiment, the porous composite media has an average flow pressure for isopropanol ranging from about 10 psi to about 130 psi.
[0110] In another aspect, the porous composite medium has a porous asymmetric polymeric flat membrane comprising one or more layers produced by solution phase inversion, thermally initiated phase separation, steam-induced phase separation, track etching, biaxial stretching, solvent etching, and combinations thereof.
[0111] In another aspect, the present invention relates to a filtration device for use in critical filtration comprising the porous composite media of the present invention.
[0112] In another aspect, the filtration device has a composite filtration medium disposed within the device such that a porous asymmetric polymeric flat sheet membrane is upstream of a retaining filter layer in the direction of filtration, whereby the porous asymmetric flat sheet membrane provides pre-filtration of the sample and the retaining filter layer provides further filtration of the sample.
[0113] In one aspect, the present invention relates to a method of sterilizing a porous, nonwoven, polymeric nanofiber-containing liquid filtration medium, the method comprising: subjecting the liquid filtration medium to at least a glass transition temperature (T g ), but the melting temperature (T m) and sterilizing the heat-treated liquid filtration medium using moist heat sterilization.
[0114] In one aspect, the present invention provides a method for removing bacteria from a liquid sample, comprising: subjecting a porous, nonwoven, polymeric nanofiber-containing liquid filtration medium to at least the glass transition temperature (T g ), but the melting temperature (T m ) or less, sterilizing the liquid filtration medium using moist heat sterilization, and passing a liquid sample containing the bacteria through the sterilized liquid filtration medium.
[0115] In one aspect, the present invention provides a method for removing viral particles from a liquid sample, comprising: subjecting a porous, nonwoven, polymeric nanofiber-containing liquid filtration medium to at least the glass transition temperature (T g ), but the melting temperature (T m ) or less, sterilizing the liquid filtration medium using moist heat sterilization, and passing a liquid sample containing viral particles through the sterile liquid filtration medium.
[0116] In another embodiment of the invention, the liquid filtration medium exhibits a viral log reduction value (LRV) of greater than about 6.
[0117] In another embodiment of the invention, the liquid filtration medium exhibits a viral log reduction value (LRV) of greater than about 3.
[0118] In another embodiment of the invention, the liquid filtration medium exhibits a viral log reduction value (LRV) of greater than about 2. [Brief description of the drawings]
[0119] [Figure 1]Figure 1 shows the difference in water permeability of selected nanofiber media before and after the sterilization process, either without (left) or with (right) heat treatment before sterilization. The shaded bar labels indicate the percent loss in water permeability after sterilization. Sterilization conditions consisted of three cycles of autoclaving, each cycle at 135°C for 60 minutes, followed by a 15 minute drying period. [Diagram 2] Figure 2 is a graph depicting a plot of the main effects of percent loss in water permeability, with each point representing the average percent loss for each factor either without (left) or with (right) heat treatment prior to sterilization. [Diagram 3] FIG. 3 shows representative scanning electron microscope (SEM) images showing the morphology of selected nanofiber media before and after the sterilization process, either without (top) or with (bottom) heat treatment before sterilization. [Figure 4] Figure 4 shows that the water permeability remains unchanged for heat-treated asymmetric nylon-66 (N66) nanofiber mats even after as many as 12 autoclaving cycles. Notably, the bubble point (BP) of the mats increases after the first three autoclaving cycles (AC-3x) and remains constant for additional autoclaving cycles. Such mats were measured to remain completely retentive to bacteria at a BP of 15 psi. [Diagram 5] Figure 5 shows representative scanning electron microscopy (SEM) images demonstrating that multiple autoclaving cycles do not substantially change the morphology of nanofibers in heat-treated asymmetric nylon-66 media (a) before sterilization, (b) after 3 autoclaving cycles, (c) after 9 autoclaving cycles, and (d) after 12 autoclaving cycles. Fiber diameters ranged from 95 to 105 nm for all conditions. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0120] <Summary>
[0121] Typically, porous filtration media are sterilized prior to aseptic use as part of the guidelines set forth by the International Council for Harmonization of Technical Requirements for Pharmaceuticals for Human Use (ICH). Of all the methods available for sterilization of porous filtration media for aseptic use, moist heat in the form of saturated steam under pressure (steam-in-place sterilization) or autoclave sterilization is the most widely used. Steam (moist heat) sterilization is non-toxic, inexpensive, rapidly germicidal, and sporicidal, making it the preferred sterilization method for aseptic use. However, such sterilization methods can adversely affect the filtration properties of the media that are important for aseptic use. Nanofiber-based liquid filtration membranes (e.g., mats) without steam sterilization can demonstrate high liquid permeability and microbial retention. However, as demonstrated herein, the morphology of nanofiber-based liquid filtration membranes can change when subjected to wet-dry processes, including conventional steam sterilization processes, potentially resulting in a dramatic loss of water permeability. It is therefore essential to design porous filtration media that are robust and can withstand wet-dry processes at room temperature (such as those used for integrity testing), steam sterilization protocols as well as dry sterilization protocols (e.g., gamma irradiation).
[0122] Without being bound to a particular theory, collapse of the nanofiber mat may occur during the drying process after the wetting agent (e.g., water or water and / or alcohol) fills the voids of the porous nanofiber mat, either during the integrity test (before the autoclave sterilization process) or by intrusion into the mat by water vapor condensation during the autoclave process. Autoclave sterilization cycles typically include a post-sterilization drying step, which occurs with a temperature ramp down. During such drying step, the liquid surface in the pores of the nanofiber mat rapidly recedes, and the surface tension (Laplace force) of the receding liquid surface pulls the nanofibers together, resulting in a three-dimensional collapse of the multi-porous structure, primarily across the thickness of the mat (in the direction of liquid evaporation). This three-dimensional collapse compresses the mat, reducing its porosity and resulting in a loss of water permeability. Nanofiber mats with smaller effective pore sizes (i.e., mats with thinner nanofibers) experience greater losses compared to mats with larger pore sizes (mats in which the nanofibers have a larger diameter). For this reason, the impact of wetting and drying processes, including moist heat sterilization, is particularly important for applications requiring filtration media containing finer nanofibers and higher retention assurance.
[0123] In certain embodiments, the filtration media and nanofiber mats disclosed herein resist structural collapse by affecting the mechanical modulus of the nanofibers, which is defined by the polymer molecular weight, orientation, and crystallinity of the nanofibers. Such strategies to increase the robustness of the nanofiber media and improve its ability to resist changes in water permeability after sterilization can include, for example, process modifications, material selection, and / or structural design. For example, in some embodiments, the effects of post-autoclaving can be mitigated by a combination of heat treatment, selection of appropriate nanofiber polymers, and / or use of asymmetric filter structures.
[0124] Thus, in certain embodiments, the methods and filtration media disclosed herein have particular relevance to the biopharmaceutical industry.In certain embodiments, methods are provided herein that can be used with as-spun porous filtration media to manufacture filter media that are sufficiently robust to withstand wet-dry processes, including steam sterilization protocols (e.g., autoclaving), and thereby reduce the processing time and cost of certain sterile filtration processes.In some embodiments, the methods provided herein can be used to create nanofiber structures that resist collapse (e.g., retain structural integrity) after moist heat sterilization.
[0125] <Definition>
[0126] For convenience, certain terms employed in the specification, examples, and appended claims are collected here.
[0127] As used herein, the singular forms "a," "an," and "the" are intended to include the plural forms as well, unless the context clearly indicates otherwise.
[0128] The term "about" means within an acceptable error range for a particular value as determined by one of ordinary skill in the art. As used herein, "about" means an amount within 10% of a given value. In other words, these values include the stated value with a 0-10% variation (X±10%) around that value.
[0129] An "asymmetric" arrangement of nanofibers or an "asymmetric nanofiber mat" may mean that the average diameter of the nanofibers in one layer of a filtration medium (e.g., a fibrous mat or support) is significantly different from the average diameter of the nanofibers in another layer of the filtration medium, or may be characterized as varying fiber diameters across the thickness of the nanofiber mat such that the average fiber diameter of one layer of the nanofiber mat is different than that of another layer of the nanofiber mat. The fiber diameter gradient across the thickness or cross-section of the nanofiber mat may also be described by an "hourglass" structure, or may be characterized as having an asymmetry such that the fiber diameters across the thickness of the nanofiber mat vary and the average fiber diameter of one layer of the nanofiber mat is different than that of another layer of the nanofiber mat. For example, the nanofiber mat may be in the form of a sheet having at least two layers (e.g., a composite filtration medium such as a composite nanofiber mat), with one layer (i.e., the "top layer") disposed on the top surface of the sheet, another layer (i.e., the "bottom layer") disposed on the bottom surface of the sheet, and optionally one or more additional layers (i.e., the "middle layer") disposed between the top and bottom layers of the nanofiber mat, where the nanofibers making up at least one of the layers have an average fiber diameter that is different from the average fiber diameter of the nanofibers in the other layer. "Asymmetric" filtration media (e.g., nanofiber mats) also include structures in which the average diameter of the nanofibers increases continuously from one surface of the media to the other (sometimes referred to as "closely woven" and "porous" layers, respectively). For example, filtration media including the nanofiber mats of the invention can be formed by simultaneously or sequentially forming nanofibers of two or more different average fiber diameters into a nonwoven structure. By varying the relative rates at which the different nanofibers are formed, an asymmetric structure can be created in which the fiber diameter changes continuously from one surface to the opposite surface. The rate of change in average fiber diameter through the thickness of the fibrous support can be "gradual" or relatively abrupt. It will be appreciated that the term "layer" refers to a region of the medium in which the average fiber diameter is relatively constant, but need not be clearly defined.In an alternative embodiment, the asymmetric arrangement of nanofibers includes nanofibers of the same average fiber diameter at different packing densities within the filtration medium. For example, layers of a composite filtration medium (e.g., a composite nanofiber mat) can be prepared from nanofibers of essentially the same average fiber diameter, except that the percentage of the total volume of each layer occupied by the nanofibers may differ. See, for example, U.S. Patent No. 4,261,834 and U.S. Patent No. 4,629,563, which are incorporated herein by reference in their entireties.
[0130] As used herein, the term "electrospinning" or "electrospun" refers to an electrostatic spinning process that produces nanofibers from a polymer solution or suspension or melt by applying an electric potential to such a solution. Electrostatic spinning processes for making electrospun nanofiber mats for filtration media, including suitable equipment for carrying out the electrostatic spinning process, are disclosed in International Publication Nos. WO2005 / 024101, WO2006 / 131081, and WO2008 / 106903, each of which is assigned to Elmarco, Liberec, Czech Republic, and each of which is fully incorporated herein by reference. "Electroblowing" describes an electrostatic spinning process in which a polymer solution discharged from a spinning nozzle is blown with a blowing gas discharged from a gas injection nozzle to form a fibrous web of fibers.
[0131] The terms "filtrate" or "permeate product," as used interchangeably herein, refer to a solution passing through a filter or membrane, such as the electrospun nanofiber compositions used herein, and a solution that has already passed through a filter or membrane.
[0132] The terms "including," "includes," "having," "has," "with," or variations thereof are inclusive in a manner similar to the term "comprising." The terms "consisting essentially of" or "consists essentially of" include embodiments that include the materials or steps specified, as well as embodiments that include materials and steps that do not materially affect the basic and novel characteristic(s) of the embodiment.
[0133] As used herein, the term "log reduction value" or "LRV" refers to the common logarithm (decimal decade) of the ratio of particle concentration in the feed to the particle concentration in the filtrate, measured under standardized conditions.
[0134] The "Bubble Point Test" provides a convenient method for measuring effective pore size. Effective pore size is calculated from the following formula:
[0135]
number
[0136] where P is the bubble point pressure, γ is the surface tension of the probe fluid, r is the pore radius, and θ is the liquid-solid contact angle. The maximum pore size (or first bubble point) is recorded when gas flow through the sample is detected, and the mean flow pore size corresponds to the calculated pore size at the pressure where the wet and semi-dry curves meet (corresponding to the pore size that accounts for 50% of the total gas flow).
[0137] Membrane manufacturers assign nominal pore size ratings to commercially available membrane filters based on their retention characteristics. As reported herein, maximum pore size is determined by the bubble point test as defined in ASTM specification F316-03, "Standard Test Methods for Pore Size Characteristics of Membrane Filters by Bubble Point and Mean Flow Pore Test," reapproved in 2011, and is reported in nanometers (nm). Unless otherwise noted, all BPs are measured using Galwick® (Porous Materials Incorporated, Ithaca, NY) as the wetting fluid.
[0138] As used herein, the term "nanofiber" refers to fibers having an average diameter or cross section of less than 1000 nm. In some embodiments, the nanofibers disclosed herein have a number average cross section of less than 800 nm, less than 700 nm, less than 600 nm, less than 500 nm, less than 400 nm, or less than 200 nm. In certain embodiments, the nanofibers disclosed herein have a number average diameter of at least 5 nm, at least 20 nm, at least 30 nm, at least 40 nm, or at least 50 nm. In certain embodiments, the nanofibers disclosed herein have a number average diameter of between 5 nm and 500 nm, between 5 nm and 200 nm, between 5 nm and 100 nm, between 5 nm and 50 nm, between 50 nm and 500 nm, or between 50 nm and 200 nm. As used herein, the term diameter includes the largest cross section of a non-round shape.
[0139] As used herein, the term "nanofiber mat" refers to a collection of a plurality of nanofibers such that the thickness of the mat is typically at least about 10 times greater than the diameter of a single fiber in the mat. The nanofibers may be randomly oriented within the mat or aligned along one or more axes.
[0140] The term "nonwoven" refers to a web comprising a plurality of randomly distributed fibers. The fibers may or may not generally be bonded to one another. The fibers may be staple or continuous. The fibers may comprise a single material or multiple materials, either as a combination of different fibers or as a combination of similar fibers each composed of a different material.
[0141] As used herein, the term "permeability" refers to the rate at which a volume of liquid passes through a given area of filtration media at a given pressure drop across the filter. A common unit of permeability is liters per square meter per hour for each psi of pressure drop, abbreviated as LMH / psi. Such measurements are obtained by forcing deionized water through a sample of said filter media having a given area. Water pressure (pressure head) or air pressure (air pressure above the water) is used to force the water through the sample.
[0142] The terms "polymer" or "polymeric" refer to relatively high molecular weight organic compounds, either natural or synthetic, whose structure may be represented by small repeating units, monomers (e.g., nylon, polyethylene, rubber, cellulose). Natural biopolymers, such as DNA and proteins, are fundamental to biological structure and function. Synthetic polymers are typically formed by addition or condensation polymerization of monomers. Nylon-6 is referred to herein as nylon-6 or N6. N66 is referred to interchangeably as N6,6, N6 / 6 or N66.
[0143] The term "porosity" is used herein to describe the degree of voids in a material and is the percentage of the total integral void volume. The percentage of porosity is calculated based on the following formula: %Porosity=100×[1−(Basis Weight / (Mat Thickness×Polymer Density))], where basis weight is in g / m 2 and the unit of polymer density is g / m 3 and the unit of mat thickness is m.
[0144] As used herein, the term "retentate" refers to the components or portions of a solution that are retained and do not pass through a filter or membrane, such as the electrospun nanofiber composition used herein, as well as the components or portions of a solution that have not yet passed through a filter or membrane. When a stirred cell is used, the liquid that contains the solutes that remain on the filter or membrane upstream layer in the stirred cell is called the "retentate." In the case of a TFF cassette or spiral device, the liquid that flows through the feed / retentate channel of the cassette or spiral device and returns from the device to the feed tank is called the retentate.
[0145] As used herein, a "semi-crystalline" polymer refers to a polymer that, when present in the solid state, contains a multiphase structure, i.e., an amorphous phase and crystalline portions of identical chemical composition but different physical properties. Upon heating, such polymers typically reach a glass transition temperature (T g ) and in the crystalline phase, the melting point temperature (T m ), whereas amorphous polymers show T g Only T m does not have.
[0146] The terms "variance" and "coefficient of variation" are used interchangeably herein and refer to a standardized measure of the dispersion of a probability or frequency distribution. It is often expressed as a percentage and is defined as the ratio of the standard deviation to the mean.
[0147] Methods for Producing Sterilizable Nonwoven Nanofiber Structures
[0148] In certain aspects, provided herein are methods for producing porous, non-woven, polymeric nanofiber-containing liquid filtration media that are compatible with moist heat sterilization. In certain embodiments, such methods include upgrading an "as-spun" nanofiber structure, as known in the art, to a moist heat sterilizable form by using a unique combination of parameters, including, for example, precise heat treatment, polymer selection, and / or specific nanofiber structure. Similarly, in certain aspects, provided herein are liquid filtration media that are compatible with moist heat sterilization, including a porous polymeric nanofiber mat disclosed herein (e.g., prepared by any of the methods disclosed herein).
[0149] In some embodiments, the porous, nonwoven, polymeric nanofiber-containing liquid filtration media (or at least the nanofiber mat comprising the filtration media) are subjected to a heat treatment in which they heat to at least the glass transition temperature (T g ), but the melting temperature (T m ) or less. Such heat treatment is preferably carried out in a non-oxidizing atmosphere, as described herein. For example, heat treatment may be carried out in an anaerobic or inert atmosphere oven, or the like, as known in the art. Transition and melting temperatures for certain exemplary polymers are provided in Table 1 and are known in the art. When glass transition or melting temperatures are provided as ranges, the midpoint of the range shall be treated as the respective temperature for purposes of this specification.
[0150] [Table 1]
[0151] In certain embodiments, the liquid filtration media (e.g., as-spun nanofiber mat) is a polymer nanofiber mat that is spun at a constant temperature. m In some embodiments, the liquid filtration medium is heated to a temperature less than the Tm In certain embodiments, the liquid filtration medium is heated to a temperature between about 1° C. and about 80° C. lower than the T m In some such embodiments, the liquid filtration medium is heated to a temperature that is about 1° C., about 5° C., about 10° C., about 15° C., about 20° C., about 25° C., about 30° C., about 35° C., about 40° C., about 45° C., about 50° C., about 55° C., about 60° C., about 65° C., about 70° C., about 75° C., or about 80° C. lower than the T of the polymeric nanofibers. m The liquid filtration medium may be heated to about 5°C to about 15°C, about 10°C to about 20°C, about 15°C to about 25°C, about 20°C to about 30°C, about 25°C to about 35°C, about 30°C to about 40°C, about 35°C to about 45°C, about 40°C to about 50°C, about 45°C to about 55°C, about 50°C to about 60°C, about 55°C to about 65°C, about 60°C to about 70°C, about 65°C to about 75°C, or about 70°C to about 80°C lower than the T of the polymer nanofibers. m In certain embodiments, the liquid filtration medium is heated to about 56° C. below the T m It is heated to about 75°C below.
[0152] In some embodiments, a liquid filtration medium comprising the polymeric nanofibers disclosed herein (or at least a nanofiber mat comprising the filtration medium) can be used that has a T of the polymeric nanofibers within the medium. g In certain embodiments, the liquid filtration medium is heated to a temperature above the T g In some embodiments, the liquid filtration medium is heated to a temperature between about 100° C. and about 200° C. higher than the T g In some such embodiments, the liquid filtration medium is heated to about 100° C., about 105° C., about 110° C., about 115° C., about 120° C., about 125° C., about 130° C., about 135° C., about 140° C., about 145° C., about 150° C., about 155° C., about 160° C., about 165° C., about 170° C., about 175° C., about 180° C., about 185° C., about 190° C., about 195° C., or about 200° C. above the T of the polymeric nanofibers. gand the like. The heating temperature is about 100°C to about 110°C, about 105°C to about 115°C, about 110°C to about 120°C, about 115°C to about 125°C, about 120°C to about 130°C, about 125°C to about 135°C, about 130°C to about 140°C, about 135°C to about 145°C, about 140°C to about 150°C, about 145°C to about 155°C, about 150°C to about 160°C, about 155°C to about 165°C, about 160°C to about 170°C, about 165°C to about 175°C, about 170°C to about 180°C, about 175°C to about 185°C, about 180°C to about 190°C, about 185°C to about 195°C, or about 190°C to about 200°C higher than the above. In certain embodiments, the liquid filtration media (e.g., polymeric nanofibers) may be sized to have a T g The temperature is increased to about 140°C to about 158°C higher than the normal temperature.
[0153] In some embodiments, the liquid filtration medium includes nylon 6 / 6 polymeric nanofibers and is heated to a temperature of about 190° C. to about 210° C. (e.g., for at least 1 hour). In some embodiments, the liquid filtration medium includes nylon 6 / 6 polymeric nanofibers and is heated to a temperature of about 208° C. (e.g., for at least 1 hour).
[0154] In certain embodiments, the nanofiber medium is heat treated for at least 1 hour, at least 2 hours, at least 3 hours, at least 4 hours, at least 5 hours, at least 6 hours, at least 7 hours, at least 8 hours, at least 9 hours, at least 10 hours, at least 11 hours, at least 12 hours, at least 13 hours, at least 14 hours, at least 15 hours, at least 16 hours, at least 17 hours, at least 18 hours, at least 19 hours, at least 20 hours, at least 21 hours, at least 22 hours, at least 23 hours, or at least 24 hours. In some embodiments, the nanofiber medium is heat treated for 2 days or less, 36 hours or less, 24 hours or less, 23 hours or less, 22 hours or less, 21 hours or less, 20 hours or less, 19 hours or less, 18 hours or less, 17 hours or less, 16 hours or less, 15 hours or less, 14 hours or less, 13 hours or less, 12 hours or less, 11 hours or less, 10 hours or less, 9 hours or less, 8 hours or less, 7 hours or less, 6 hours or less, 5 hours or less, or 1 hour or less. In certain embodiments, the nanofiber medium is heat treated for about 1 hour, about 2 hours, about 3 hours, about 1 hour, about 5 hours, about 6 hours, about 7 hours, about 8 hours, about 9 hours, about 10 hours, about 11 hours, about 12 hours, about 13 hours, about 14 hours, about 15 hours, about 16 hours, about 17 hours, about 18 hours, about 19 hours, about 20 hours, about 21 hours, about 22 hours, about 23 hours, or about 24 hours. In certain embodiments, the nanofiber medium is heat treated for 1 hour to 21 hours, 1 hour to 18 hours, 1 hour to 12 hours, or 1 hour to 6 hours.
[0155] In some embodiments, the liquid filtration media disclosed herein are comprised of asymmetric nanofiber mats that exhibit fiber diameters that vary across the thickness of the nanofiber mat, such that the average fiber diameter of one layer of the nanofiber mat is different from that of the other layer of the nanofiber mat. Alternatively, the asymmetric nanofiber structure may be a composite multi-layer structure, where the layer(s) of one layer can have a different average fiber diameter than the layer(s) of the other layer. The two "external" surface layers have a different average fiber diameter than the "internal" layer. The "external" surface is defined as the one that contacts the spinning substrate or faces the nanofiber-generating electrode. Anything between the two external surfaces is defined as an internal layer. In certain embodiments, the ratio of the average fiber diameter of one layer of the asymmetric nanofiber mat to the other layer is at least 1-2. In some embodiments, the ratio of the average fiber diameters is at least 1-1.75, 1-1.5, 1-1.25, or 1-1.15. Thus, in certain embodiments, the ratio of the average fiber diameter of one layer of the asymmetric nanofiber mat to the other layer is at least 1.15.
[0156] The asymmetric nanofiber structures disclosed herein may have an average fiber diameter of about 5 nm to about 1,000 nm for at least one layer. Thus, the asymmetric nanofiber structures may have a nanofiber diameter of about 1000 nm, 950 nm, 900 nm, 850 nm, 800 nm, 750 nm, 700 nm, 650 nm, 600 nm, 550 nm, 500 nm, 450 nm, 400 nm, 350 nm, 300 nm, 250 nm, 200 nm, 150 nm, 100 nm, 90 nm, 80 nm, 70 nm, 60 nm, 50 nm, 40 nm, 30 nm, or 20 nm for at least one layer. In some embodiments, the average diameter of the nanofibers is 5 nm to 20 nm, 15 nm to 25 nm, 20 nm to 30 nm, 25 nm to 35 nm, 30 nm to 40 nm, 35 nm to 45 nm, 40 nm to 50 nm, 45 nm to 55 nm, 50 nm to 60 nm, 55 nm to 65 nm, 60 nm to 70 nm, 65 nm to 75 nm, 70 nm to 80 nm, 75 nm to 85 nm, 80nm~90nm, 85nm~95nm, 90nm~100nm, 95nm~105nm, 100nm~110nm, 105nm~115nm, 115nm~120nm, 115nm~125nm, 1 20nm~130nm, 125nm~135nm, 130nm~140nm, 135nm~145nm, 140nm~150nm, 145nm~155nm, 150nm~160nm, 155nm~16 5nm, 160nm~170nm, 165nm~175nm, 170nm~180nm, 175nm~185nm, 180nm~190nm, 185nm~195nm, 190nm~200nm, 195 nm~205nm, 200nm~210nm, 205nm~215nm, 210nm~220nm, 215nm~225nm, 220nm~230nm, 225nm~235nm, 230nm~240n m, 235nm~245nm, 240nm~250nm, 245nm~255nm, 250nm~260nm, 255nm~265nm, 260nm~270nm, 265nm~275nm, 270nm ~280nm, 275nm~285nm, 280nm~290nm, 285nm~295nm, 290nm~300nm, 295nm~305nm, 300nm~310nm, 305nm~315nm,310nm~320nm, 315nm~325nm, 320nm~330nm, 325nm~335nm, 330nm~340nm, 335nm~345nm, 340nm~350 nm, 345nm~355nm, 350nm~360nm, 355nm~365nm, 360nm~370nm, 365nm~375nm, 370nm~380nm, 375nm~3 85nm, 380nm~390nm, 385nm~395nm, 390nm~400nm, 395nm~405nm, 400nm~410nm, 405nm~415nm, 410n m~420nm, 415nm~425nm, 420nm~430nm, 425nm~435nm, 430nm~440nm, 435nm~445nm, 440nm~450nm, 44 5nm~455nm, 450nm~460nm, 455nm~465nm, 460nm~470nm, 465nm~475nm, 470nm~480nm, 475nm~485nm , 480nm~490nm, 485nm~495nm, 490nm~500nm, 500nm~550nm, 525nm~575nm, 550nm~600nm, 575nm~625 nm, 600 nm to 650 nm, 625 nm to 675 nm, 650 nm to 700 nm, 675 nm to 725 nm, 700 nm to 750 nm, 725 nm to 775 nm, 750 nm to 800 nm, 775 nm to 825 nm, 800 nm to 850 nm, 825 nm to 875 nm, 850 nm to 900 nm, 925 nm to 975 nm, or 950 nm to 1000 nm. In yet another embodiment, the average fiber diameter is less than about 5 nm for at least one layer of the asymmetric nanofiber structure.
[0157] In some embodiments, the nanofibers and / or the solution from which they are spun (or blown) comprise a polymer or polymer blend. For example, in some embodiments, the polymer or polymer blend is a semi-crystalline polymer. In some embodiments, the polymer or polymer blend is nylon-6, nylon-6,6, nylon 6,6-6,10, nylon-6 copolymer, nylon-6,6 copolymer, nylon 6,6-6,10 copolymer, and any mixtures thereof. In certain embodiments, the polymer is nylon 6 or nylon 6,6. In some embodiments, the polymer is nylon 6,6.
[0158] In some embodiments, the polymer or polymer blend is selected from thermoplastic polymers, thermosetting polymers, nylons, polyimides, aliphatic polyamides, aromatic polyamides, polysulfones, cellulose acetate, polyethersulfones, polyurethanes, poly(urea urethanes), polybenzimidazoles, polyetherimides, polyacrylonitriles, poly(ethylene terephthalate), polypropylene, polyaniline, poly(ethylene oxide), poly(ethylene naphthalate), poly(butylene terephthalate), styrene butadiene rubber, polystyrene, poly(vinyl chloride), poly(vinyl alcohol), poly(vinylidene fluoride), poly(vinyl butylene), and copolymers, derivatives, or blends thereof. As used herein, the term "nylon" can include nylon-6, nylon-6,6, nylon 6,6-6,10, and copolymers, derivatives, blends, and combinations thereof.
[0159] In some embodiments, the polymer or polymer blend is selected from the group consisting of nylon-6, nylon-4,6, nylon-6,6, nylon-6,6-6,10, polyaramid, polyurethane (PU), polybenzimidazole, polycarbonate, polyacrylonitrile, polyvinyl alcohol, polylactic acid (PLA), polyethylene-co-vinyl acetate (PEVA), PEVA / PLA, polymethyl methacrylate (PMMA), PMMA / tetrahydroperfluorooctyl acrylate (TAN), polyethylene oxide (PEO), collagen-PEO, polystyrene (PS), polyaniline (PANI) / PEO, PANI / PS, polyvinylcarbazole, polyethylene terephthalate (PET), polyacrylic acid-polypyrene methanol (PAA-PM), polyamide (PA), silk / PEO, polyvinyl phenol (PVP), polyvinyl chloride (PVC), cellulose acetate (CA), PAA-PM / PU, polyvinyl alcohol (PVA) / silica, poly poly(lactic-co-glycolic acid) (PLGA), polycaprolactone, poly(2-hydroxyethyl methacrylate) (HEMA), poly(vinylidene difluoride) (PVDF), PVDF / PMMA, polyetherimide (PEI), polyethylene glycol (PEG), poly(poy)(ferrocenyldimethylsilane) (PFDMS), nylon 6 / montmorillonite (Mt), poly(ethylene-co-vinyl alcohol), polyacrylonitrile (PAN) / TiO2, polycaprolactone (PCL) / metal, polyvinylpyrrolidone, polymetaphenylene isophthalamide, polyethylene (PE), polypropylene (PP), nylon-12, polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polyethersulfone (PES), polyvinyl butyral (PVB), PET / PEN, and copolymers, derivatives or blends thereof.
[0160] The liquid filtration media disclosed herein can be produced by electrospinning or electroblowing a polymer solution or melt to produce a porous, non-woven polymeric nanofiber structure, such as a nanofiber mat. Preferably, the liquid filtration media is produced by electrospinning, and the resulting porous, non-woven polymeric nanofiber mat comprises one or more polymers. Electrospinning is a process for producing nanofibers from a mixture of polymers, such as a polymer solution, suspension, or polymer melt. The process involves applying an electric potential to such a polymer solution or polymer melt. Specific details of the electrospinning process for making electrospun nanofiber mats or membranes, including suitable equipment for carrying out the electrospinning process, are described in International Patent Application Publication Nos. WO2005 / 024101, WO2006 / 131081, and WO2008 / 106903, each of which is incorporated herein by reference in its entirety.
[0161] In the electrospinning process, fibers are generated from a spinning electrode by applying a high voltage to the electrode and the polymer solution, where the fibers are electrically charged, spun towards a collecting electrode, and collected as a highly porous nonwoven mat on the substrate between the electrodes. When the polymer solution discharged from the spinning nozzle is blown onto the substrate with a blowing gas discharged from a gas injection nozzle, it is called electroblowing.
[0162] The disclosed nanofiber mats can have a thickness of about 1 μm to about 500 μm. In some embodiments, the nanofiber mats have a thickness of at least 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm, 80 μm, 85 μm, 90 μm, 95 μm, 100 μm, 105 μm, 110 μm, 115 μm, 120 μm, 125μm, 130μm, 135μm, 140μm, 145μm, 150μm, 155μm, 160μm, 165μm, 170μm, 175μm, 180μm, 185μm , 190μm, 195μm, 200μm, 205μm, 210μm, 215μm, 220μm, 225μm, 230μm, 235μm, 240μm, 245μm, 250μm , 255μm, 260μm, 265μm, 270μm, 275μm, 280μm, 285μm, 290μm, 295μm, 300μm, 305μm, 310μm, 315μ m, 320μm, 325μm, 330μm, 335μm, 340μm, 345μm, 350μm, 355μm, 360μm, 365μm, 370μm, 375μm, 380μ The thickness may be 385 μm, 390 μm, 395 μm, 400 μm, 405 μm, 410 μm, 415 μm, 420 μm, 425 μm, 430 μm, 435 μm, 440 μm, 445 μm, 450 μm, 455 μm, 460 μm, 465 μm, 470 μm, 475 μm, 480 μm, 485 μm, 490 μm, 495 μm or 500 μm.
[0163] In some embodiments, the fabricated nanofiber structures of the liquid filtration media (e.g., nanofiber mats) disclosed herein have an average fiber diameter of about 5 nm to about 1,000 nm. The fiber diameters may have a broad distribution of 16-36% CoV. In some such embodiments, the average nanofiber diameter is 1000 nm, 950 nm, 900 nm, 850 nm, 800 nm, 750 nm, 700 nm, 650 nm, 600 nm, 550 nm, 500 nm, 450 nm, 400 nm, 350 nm, 300 nm, 250 nm, 200 nm, 150 nm, 100 nm, 90 nm, 80 nm, 70 nm, 60 nm, 50 nm, 40 nm, 30 nm, or 20 nm or less. In some embodiments, the average nanofiber diameter is 5 nm to 20 nm, 15 nm to 25 nm, 20 nm to 30 nm, 25 nm to 35 nm, 30 nm to 40 nm, 35 nm to 45 nm, 40 nm to 50 nm, 45 nm to 55 nm, 50 nm to 60 nm, 55 nm to 65 nm, 60 nm to 70 nm, 65 nm to 75 nm, 70 nm to 80 nm, 75 nm to 85 nm, 80 nm to 90 nm, m, 85nm~95nm, 90nm~100nm, 95nm~105nm, 100nm~110nm, 105nm~115nm, 110nm~120nm, 115nm~125nm, 120n m~130nm, 125nm~135nm, 130~140nm, 135~145nm, 140nm~150nm, 145~155nm, 150nm~160nm, 155nm~165nm, 1 60nm~170nm, 165nm~175nm, 170nm~180nm, 175nm~185nm, 180nm~190nm, 185nm~195nm, 190nm~200nm, 195 nm~205nm, 200nm~210nm, 205nm~215nm, 210nm~220nm, 215nm~225nm, 220nm~230nm, 225nm~235nm, 230nm~ 240nm, 235nm~245nm, 240nm~250nm, 245nm~255nm, 250nm~260nm, 255nm~265nm, 260nm~270nm, 265nm~27 5nm, 270nm~280nm, 275nm~285nm, 280m~290nm, 285nm~295nm, 290nm~300nm, 295nm~305nm, 300nm~310nm,305nm~315nm, 310nm~320nm, 315nm~325nm, 320nm~330nm, 325nm~335nm, 330nm~340nm, 335nm~345n m, 340nm~350nm, 345nm~355nm, 350nm~360nm, 355nm~365nm, 360nm~370nm, 365nm~375nm, 370nm~380 nm, 375nm~385nm, 380m~390nm, 385nm~395nm, 390nm~400nm, 395nm~405nm, 400nm~410nm, 405nm~415 nm, 410nm~420nm, 415nm~425nm, 420nm~435nm, 425nm~435nm, 430nm~440nm, 435nm~445nm, 440nm~45 0nm, 445nm~455nm, 450nm~460nm, 455nm~465nm, 460nm~470nm, 465nm~475nm, 470nm~480nm, 475nm~4 85nm, 480m~490nm, 485nm~495nm, 490nm~500nm, 500nm~550nm, 525nm~575nm, 550nm~600nm, 575nm~6 25 nm, 600 nm to 650 nm, 625 nm to 675 nm, 650 nm to 700 nm, 675 nm to 725 nm, 700 nm to 750 nm, 725 nm to 775 nm, 750 nm to 800 nm, 775 nm to 825 nm, 800 nm to 850 nm, 825 nm to 875 nm, 850 nm to 900 nm, 925 nm to 975 nm, or 950 nm to 1000 nm. In yet another embodiment, the average fiber diameter is less than about 5 nm.
[0164] Two desirable characteristics of a liquid filtration membrane are high permeability and reliable retention. In certain embodiments, the electrospun nanofiber media disclosed herein are highly porous polymeric materials, where the "pore" size is linearly proportional to the fiber diameter, while the porosity is relatively independent of the fiber diameter. In certain embodiments, the porosity of the electrospun nanofiber media falls within the range of about 70%-95% (e.g., about 75%-95%, about 80%-95%). In some embodiments, the electrospun nanofiber media provided herein have significantly higher permeability than dip-cast membranes of similar thickness and pore size ratings.
[0165] In some embodiments, the liquid filtration media (e.g., nanofiber mats) provided herein have a bubble point (BP) (i.e., as determined by the Bubble Point test set forth in ASTM Specification F316-03, "Standard Test Methods for Pore Size Characteristics of Membrane Filters by Bubble Point and Mean Flow Pore Test," reapproved in 2011) of 5 psi to 150 psi, e.g., 10 psi, 11 psi, 12 psi, 13 psi, 14 psi, 15 psi, 16 psi, 17 psi, 18 psi, 19 psi, 20 psi, 21 psi, 22 psi, 23 psi, 24 psi, 25 psi, 50 psi, 75 psi, 100 psi, 125 psi, or 150 psi, using Galwick® as the wetting fluid.
[0166] In some embodiments, the nanofiber structures (e.g., nanofiber mats) have a maximum pore size as determined by a bubble point test of 500 nm, 450 nm, 400 nm, 350 nm, 300 nm, 250 nm, 200 nm, 150 nm, 100 nm, or less than 50 nm. In some embodiments, the nanofiber structures (e.g., nanofiber mats) produced have a maximum pore size as determined by a bubble point test of 5 nm to 20 nm, 15 nm to 25 nm, 20 nm to 30 nm, 25 nm to 35 nm, 30 nm to 40 nm, 35 nm to 45 nm, 40 nm to 50 nm, 45 nm to 55 nm, 50 nm to 60 nm, 55 nm to 65 nm, 60 nm to 70 nm, 65 nm to 75 nm, 70 nm to 80 nm, 75 nm to 85 nm, 80 nm to 90 nm, 85 nm to 95 nm, 90 nm to 100 nm, 90 nm to 100 nm, 90 nm to 150 nm, 90 nm to 200 nm, 90 nm to 250 nm, 90 nm to 300 nm, 90 nm to 350 nm, 90 nm to 400 nm, 90 nm to 500 nm, 90 nm to 250 nm, 90 nm to 350 nm, 90 nm to 400 nm, 90 nm to 500 nm, 90 nm to 1000 nm, 90 nm to 250 nm, 90 nm to 350 nm, 90 nm to 400 nm, 90 nm to 500 nm, 90 nm to 250 nm, 90 nm to 350 5nm~105nm, 100nm~110nm, 105nm~115nm, 110nm~120nm, 115nm~125nm, 120nm~130nm, 125nm~135nm, 130~140nm, 135~145nm, 140nm~ 150nm, 145~155nm, 150nm~160nm, 155nm~165nm, 160nm~170nm, 165nm~175nm, 170nm~180nm, 175nm~185nm, 180nm~190nm, 185nm~195 nm, 190nm~200nm, 195nm~205nm, 200nm~210nm, 205nm~215nm, 210nm~220nm, 215nm~225nm, 220nm~230nm, 225nm~235nm, 230nm~240 nm, 235nm~245nm, 240nm~250nm, 245nm~255nm, 250nm~260nm, 255nm~265nm, 260nm~270nm, 265nm~275nm, 270nm~280nm, 275nm~285n m, 280m~290nm, 285nm~295nm, 290nm~300nm, 295nm~305nm, 300nm~310nm, 305nm~315nm, 310nm~320nm, 315nm~325nm, 320nm~330nm , 325nm~335nm, 330nm~340nm, 335nm~345nm, 340nm~350nm, 345nm~355nm, 350nm~360nm, 355nm~365nm, 360nm~370nm, 365nm~375nm,370nm~380nm, 375nm~385nm, 380m~390nm, 385nm~395nm, 390nm~400nm, 395nm~405nm, 400nm~410 nm, 405nm~415nm, 410nm~420nm, 415nm~425nm, 420nm~430nm, 425nm~435nm, 430nm~440nm, 435nm~ It has a maximum pore size determined by a bubble point test of 445nm, 440nm to 450nm, 445nm to 455nm, 450nm to 460nm, 455nm to 465nm, 460nm to 470nm, 465nm to 475nm, 470nm to 480nm, 475nm to 485nm, 480nm to 490nm, 485nm to 495nm, or 490nm to 500nm.
[0167] In some embodiments, the liquid filtration medium (e.g., nanofiber mat) has a porosity of at least 70%, at least 75%, at least 80%, at least 85%, at least 90%, or at least 95%. In some embodiments, the porosity is between 70% and 95%, between 75% and 95%, between 80% and 95%, between 85% and 95%, or between 90% and 95%.
[0168] In some embodiments, the liquid filtration medium (e.g., nanofiber mat) has a fiber diameter variation of 30% or less, 29% or less, 28% or less, 27% or less, 26% or less, 25% or less, 24% or less, 23% or less, 22% or less, 21% or less, 20% or less, 19% or less, 18% or less, or 17% or less.
[0169] In some embodiments, the liquid filtration medium (e.g., nanofiber mat) has a permeability of at least 10 LMH / psi to 20,000 LMH / psi. In some embodiments, the liquid filtration medium (e.g., nanofiber mat) has a permeability of at least 10 LMH / psi to 20,000 LMH / psi. In some such embodiments, the liquid filtration media is at least 6000 LMH / psi, at least 5750 LMH / psi, at least 5500 LMH / psi, at least 5250 LMH / psi, at least 5000 LMH / psi, at least 4750 LMH / psi, at least 4500 LMH / psi, at least 4250 LMH / psi, at least 4000 LMH / psi, at least 3750 LMH / psi, at least 3500 LMH / psi, at least 3250 LMH / psi, at least 3000 LMH / psi, at least 2750 LMH / psi, at least 2500 LMH / psi, at least 2250 LMH / psi, at least 2000 LMH / psi, at least 1750 LMH / psi, at least 1500 LMH / psi, at least 1250 LMH / psi, at least 1000 LMH / psi, at least 975 LMH / psi, at least 950 LMH / psi, at least 925LMH / psi, at least 900LMH / psi, at least 875LMH / psi, at least 850LMH / psi, at least 825LMH / psi, at least 800LMH / psi, at least 775LMH / psi, at least 750LMH / psi, at least 725LMH / psi, at least 700LMH / psi, at least 675LMH / psi, at least 650LMH / psi, at least 625LMH / psi, at least 600LMH / psi, at least 575LMH / psi, at least 550LMH / psi, at least 525LMH / psi, at least 500LMH / psi, at least 475LMH / psi, at least 450LMH / psi, at least 425LMH / psi, at least 400LMH / psi, at least 375LMH / psi, at least 350LMH / psi, at least 325LMH / psi,In some embodiments, the liquid filtration medium has a permeability of at least 300 LMH / psi, or at least 100 LMH / psi, or at least 10 LMH / psi. In some embodiments, the liquid filtration medium has a permeability of at least 300 LMH / psi to at least 400 LMH / psi, at least 450 LMH / psi to at least 550 LMH / psi, at least 400 LMH / psi to at least 500 LMH / psi, at least 550 LMH / psi to at least 650 LMH / psi, at least 700 LMH / psi to at least 800 LMH / psi, at least 750 LMH / psi to at least 850 LMH / psi, at least 900 LMH / psi to at least 1000 LMH / psi. At least 1000LMH / psi, at least 850LMH / psi to at least 950LMH / psi, at least 1000LMH / psi to at least 1050LMH / psi, at least 1100LMH / psi to at least 1200LMH / psi, at least 1150LMH / psi to at least 1250LMH / psi, at least 1200LMH / psi to at least 1300LMH / psi, at least 1250LMH / psi to at least 1350LMH / psi, at least 1300LMH / psi psi~at least 1400LMH / psi, at least 1350LMH / psi~at least 1450LMH / psi, at least 1400LMH / psi~at least 1500LMH / psi, at least 1450LMH / psi~at least 1550LMH / psi, at least 1500LMH / psi~at least 1600LMH / psi, at least 1550LMH / psi~at least 1650LMH / psi, at least 1600LMH / psi~at least 1700LMH / psi, at least 1 650LMH / psi ~ at least 1750LMH / psi, at least 1700LMH / psi ~ at least 1800LMH / psi, at least 1750LMH / psi ~ at least 1850LMH / psi, at least 1900LMH / psi ~ at least 2000LMH / psi, at least 1950LMH / psi ~ at least 2050LMH / psi, at least 2100LMH / psi ~ at least 2200LMH / psi, at least 2150LMH / psi ~ at least 2250LMH / psi,At least 2200LMH / psi~at least 2300LMH / psi, at least 2250LMH / psi~at least 2350LMH / psi, at least 2300LMH / psi~at least 2400LMH / psi, at least 2350LMH / psi~at least 2450LMH / psi, at least 2400LMH / psi~at least 2500LMH / psi, at least 2450LMH / psi~at least 2550LMH / psi, at least 2500LMH / psi~at least 2600LMH / psi, at least 255 0LMH / psi~at least 2650LMH / psi, at least 2600LMH / psi~at least 2700LMH / psi, at least 2650LMH / psi~at least 2750LMH / psi, at least 2700LMH / psi~at least 2800LMH / psi, at least 2750LMH / psi~at least 2850LMH / psi, at least 2900LMH / psi~at least 3000LMH / psi, at least 2950LMH / psi~at least 3050LMH / psi, at least 3100LMH / psi~ At least 3200LMH / psi, at least 3150LMH / psi~at least 3250LMH / psi, at least 3200LMH / psi~at least 3300LMH / psi, at least 3250LMH / psi~at least 3350LMH / psi, at least 3300LMH / psi~at least 3400LMH / psi, at least 3350LMH / psi~at least 3450LMH / psi, at least 3400LMH / psi~at least 3500LMH / psi, at least 3450LMH / psi~at least 355 0LMH / psi, at least 3500LMH / psi~at least 3600LMH / psi, at least 3550LMH / psi~at least 3650LMH / psi, at least 3600LMH / psi~at least 3700LMH / psi, at least 3650LMH / psi~at least 3750LMH / psi, at least 3700LMH / psi~at least 3800LMH / psi, at least 3750LMH / psi~at least 3850LMH / psi, at least 3900LMH / psi~at least 4000LMH / psi,At least 3950LMH / psi~at least 4050LMH / psi, at least 4100LMH / psi~at least 4200LMH / psi, at least 4150LMH / psi~at least 4250LMH / psi, at least 4200LMH / psi~at least 4300LMH / psi, at least 4250LMH / psi~at least 4350LMH / psi, at least 4300LMH / psi~at least 4400LMH / psi, at least 4350LMH / psi~at least 4450LMH / psi, at least 440 0LMH / psi~at least 4500LMH / psi, at least 4450LMH / psi~at least 4550LMH / psi, at least 4500LMH / psi~at least 4600LMH / psi, at least 4550LMH / psi~at least 4650LMH / psi, at least 4600LMH / psi~at least 4700LMH / psi, at least 4650LMH / psi~at least 4750LMH / psi, at least 4700LMH / psi~at least 4800LMH / psi, at least 4750LMH / psi~ At least 4850LMH / psi, at least 4900LMH / psi~at least 5000LMH / psi, at least 4950LMH / psi~at least 5050LMH / psi, at least 5100LMH / psi~at least 5200LMH / psi, at least 5150LMH / psi~at least 5250LMH / psi, at least 5200LMH / psi~at least 5300LMH / psi, at least 5250LMH / psi~at least 5350LMH / psi, at least 5300LMH / psi~at least 540 0LMH / psi, at least 5350LMH / psi~at least 5450LMH / psi, at least 5400LMH / psi~at least 5500LMH / psi, at least 5450LMH / psi~at least 5550LMH / psi, at least 5500LMH / psi~at least 5600LMH / psi, at least 5550LMH / psi~at least 5650LMH / psi, at least 5600LMH / psi~at least 5700LMH / psi, at least 5650LMH / psi~at least 5750LMH / psi,It has a permeability of at least 5700 LMH / psi to at least 5800 LMH / psi, at least 5750 LMH / psi to at least 5850 LMH / psi, at least 5900 LMH / psi to at least 6000 LMH / psi, or at least 5950 LMH / psi, at least 6000 LMH / psi, at least 7000 LMH / psi, at least 8000 LMH / psi, at least 9000 LMH / psi, at least 10,000 LMH / psi, at least 12,000 LMH / psi, at least 14,000 LMH / psi, at least 16,000 LMH / psi, at least 18,000 LMH / psi, or at least 20,000 LMH / psi.
[0170] A quantitative measure of microbial retention by a filtration membrane is usually expressed as a log reduction value, sometimes called the log retention value or LRV. LRV is the ratio of the particle concentration in the challenge solution to the particle concentration in the filter effluent: LRV = Log{[CFU] challenge / [CFU] effluent} is the logarithm of
[0171] If a filter retains all microorganisms under the test conditions, we typically report an LRV that exceeds the value obtained when one microorganism passes through the filter. For example, a challenge particle concentration of 4.77 x 10 7 CFU / cm 2 So the effective filter area is 13.8cm 2 The maximum measurable LRV for this device is 8.22. If particles do not pass through the filter, the LRV is reported as greater than 8.22.
[0172] The pore size rating of a membrane is an indication of whether the membrane has successfully passed the relevant standardized bacterial challenge test. The most common pore size rating is 0.22 μm, which is assigned to membranes that have passed the Standard Test Method for Measuring Bacterial Retention of Membrane Filters Used in Liquid Filtration (ASTM F838-83 test), and is ≧10 7 CFU / cm 2The liquid filtration media disclosed herein can be certified to produce a sterile effluent after being challenged with Brevundzimonas diminuta. Brevundzimonas diminuta (ATTC#19146), formerly known as Pseudomonas diminuta, is an aerobic gram-negative bacillus (bacillus). Due to its small size, B. diminuta is the standard microorganism for validation of sterilizing membrane filters and the like. Thus, the liquid filtration media disclosed herein have a Brevundzimonas diminuta log reduction value (LRV) of at least 1 as measured according to ASTM F838-83. Alternatively, the liquid filtration media disclosed herein have a Brevundzimonas diminuta log reduction value (LRV) of at least 8 as measured according to ASTM F838-83. Preferably, the liquid filtration media exhibits complete retention of the microorganism, e.g., Brevundzimonas diminuta, as measured according to ASTM F838-83. In certain embodiments, the liquid filtration media is challenged with virus particles and exhibits a virus log reduction value (LRV) of greater than about 6. In certain other embodiments, the liquid filtration media disclosed herein are capable of purifying biological materials of interest, including virus-like particles, proteins, and associated polysaccharides, such as those found in vaccines. Generally, biological materials have a molecular weight of about 500 KDa or greater. Thus, the liquid filtration media disclosed herein can exhibit retention of standardized macromolecules and / or particles of a certain size, such as the use of dextran in standard methods such as "dextran sieving."
[0173] In some embodiments, the liquid filtration medium (e.g., porous nonwoven nanofiber-containing liquid filtration medium) further comprises a porous nonwoven support. The nanofibers can be electrospun or electroblown onto the surface of the porous nonwoven support, where the root mean square height of the surface of the porous nonwoven support is less than about 70 μm. In some such embodiments, the support comprises one or more layers manufactured by meltblowing, wet laying, spunbonding, calendaring, electrospinning, electroblowing, or any combination thereof. The support may comprise a thermoplastic polymer, a polyolefin, a polypropylene, a polyester, a polyamide, a copolymer thereof, a polymer blend, or any combination thereof. Preferably, the densest pore size of the nanofiber layer is smaller than the densest pore size of the porous nonwoven support.
[0174] In some embodiments, the porous support comprises one or more layers selected from the group consisting of spunbonded nonwovens, meltblown nonwovens, needlepunched nonwovens, spunlaced nonwovens, wetlaid nonwovens, resin-bonded nonwovens, electrospun, electroblowing, woven fabrics, knitted fabrics, paper (including surface-modified paper), and any combination thereof.
[0175] In some embodiments, provided herein is a porous composite medium comprising a porous asymmetric polyethersulfone (PES) flat thin film prefilter and a retentive layer comprising a liquid filtration medium prepared by any of the methods disclosed herein. In some embodiments, the porous asymmetric PES flat membrane prefilter has a dense layer and a porous layer with pore sizes that increase in size between the dense layer and the porous layer. The retentive layer comprising a liquid filtration medium disclosed herein may be disposed on the dense layer of the porous asymmetric PES flat membrane. In a preferred embodiment, the pore size of the retentive layer is smaller than the pore size of the dense layer of the porous asymmetric PES flat membrane prefilter. In some such embodiments, the porous composite medium has a bubble point measured with a liquid that is at least 20% greater than the bubble point of the porous flat membrane prefilter alone. Preferably, the porous composite medium has a mean flow bubble point for isopropanol in the range of about 10 psi to about 130 psi. In some embodiments, the porous asymmetric PES flat membrane disclosed herein comprises one or more layers produced by solution phase inversion, thermally initiated phase separation, steam-induced phase separation, track etching, biaxial stretching, solvent etching, and combinations thereof.Therefore, a filtration device for use in critical filtration is provided herein, comprising such a porous composite medium disclosed herein.In such a critical filtration device, the porous asymmetric PES flat membrane can provide pre-filtration of a sample, while the retaining filter layer provides further filtration of the sample.In some such embodiments, the porous composite filtration medium is preferably arranged such that the porous asymmetric PES flat membrane is upstream of the retaining filter layer in the direction of filtration.
[0176] In particular, the liquid filtration media disclosed herein (e.g., heat treated porous nonwoven asymmetric polymeric nanofiber-containing liquid filtration media) are compatible with moist heat sterilization. Moist heat is typically used in connection with aseptic applications, such as those commonly practiced in the biopharmaceutical industry. Such effects of wet-dry processes, including moist heat sterilization methods as known in the art, include, but are not limited to, saturated steam flowing under pressure (i.e., steam-in-place sterilization), autoclave sterilization, and tindarization. Preferably, the liquid filtration media are compatible with autoclave sterilization such that they resist changes in nanofiber structure (e.g., nanofiber morphology) and filtration parameters (e.g., permeability, porosity, LRV, and BP) described herein.
[0177] In some embodiments, the liquid filtration media provided herein resist a change in liquid permeability after sterilization relative to a corresponding filtration media that does not include semi-crystalline polymeric nanofibers, does not include asymmetric nanofiber structures, is not heat treated, or any combination thereof. In some such embodiments, the sterilized liquid filtration media exhibits a 15% or less decrease in liquid permeability after sterilization. For example, autoclaved liquid filtration media of the present invention (e.g., autoclaved at least once or up to at least 12 times) do not exhibit a change in liquid permeability. Preferably, such sterilized liquid filtration media exhibits a 1% to 15% or less decrease in liquid permeability, e.g., a 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, or 15% decrease in liquid permeability. More preferably, the disclosed sterilized liquid filtration media exhibits a 11% or less decrease in liquid permeability. In a most preferred embodiment, the sterilized liquid filtration medium (e.g., autoclaved at least once or at least 12 times) exhibits an increase in liquid permeability, such as at least a 1% to 6% increase in liquid permeability. Preferably, the sterilized liquid filtration medium exhibits an increase in liquid permeability of at least 6%.
[0178] Similarly, a sterilized liquid filtration medium (e.g., autoclaved at least once or at least up to 12 times) resists a change in bubble point (BP) as disclosed herein. In some such embodiments, the sterilized liquid filtration medium does not exhibit a change in BP. For example, but not limited to, the sterilized liquid filtration medium exhibits or maintains a BP of 5 psi to 150 psi. Preferably, the sterilized liquid filtration medium exhibits or maintains a bubble point of 20 psi or greater. Most preferably, the liquid filtration medium exhibits less change in BP after sterilization compared to a corresponding filtration medium that does not include semi-crystalline polymer nanofibers, does not include an asymmetric nanofiber structure, is not heat treated, or any combination thereof. In some such embodiments, the BP is measured using water. In a preferred embodiment, the BP is measured using an alcohol (e.g., ethanol and / or isopropyl alcohol). In a more preferred embodiment, the BP is measured using a solution that includes water and alcohol. Most preferably, the BP is measured using Galwick® wetting fluid.
[0179] In some embodiments, sterilized liquid filtration media (e.g., autoclaved at least once or at least 12 times) resist changes in porosity. Preferably, such sterilized liquid filtration media exhibit or maintain a porosity of about 80% to about 95%.
[0180] In some embodiments, the sterilized liquid filtration medium (e.g., autoclaved at least once or at least 12 times) has or maintains its log reduction value (LRV). In a preferred embodiment, the sterilized liquid filtration medium has an LRV for Brevizimonas diminuta of at least 8 as measured according to ASTM F838-83. More preferably, the sterilized liquid filtration medium exhibits complete retention of the microorganism.
[0181] In a further aspect of the present invention, there is provided a method for removing bacteria from a liquid sample, comprising: filtration of a porous, nonwoven, polymeric nanofiber-containing liquid filtration medium as disclosed herein with at least T of the polymeric nanofibers. g However, T m Disclosed herein is a method comprising heating the liquid filtration medium to a temperature of at least 100° C. for at least 1 hour, preferably in a non-oxidizing environment such as an inert atmosphere oven. The heat-treated liquid filtration medium is then sterilized using moist heat sterilization, such as autoclaving, and a liquid sample containing bacteria is passed through the sterilized liquid filtration medium. In a preferred embodiment, the liquid filtration medium exhibits a log reduction value (LRV) of at least 8 for Brevundzimonas diminuta as measured according to ASTM F838-83 before and / or after autoclaving.
[0182] Similarly, certain embodiments of the present invention include a method for removing viral particles from a liquid sample, the method comprising: filtration of a porous, nonwoven, polymeric nanofiber-containing liquid filtration medium as disclosed herein with at least T of the polymeric nanofibers. g However, T m The heat treatment may be performed for at least 1 hour, preferably in a non-oxidizing environment such as an inert atmosphere oven. Similarly, the heat-treated liquid filtration medium is then sterilized using moist heat sterilization, such as autoclaving, and a liquid sample containing viral particles is passed through the sterilized liquid filtration medium. In some such embodiments, the liquid filtration medium exhibits a viral log reduction value (LRV) of greater than about 6 before and / or after autoclaving.
[0183] <Test Method>
[0184] As reported herein, basis weight is determined in accordance with ASTM procedure D-3776 / D3776M-09a(2017) "Standard Test Methods for Mass Per Unit Area (Weight) of Fabric" and is expressed in g / m 2Report in.
[0185] As reported herein, porosity is in g / m 2 The basis weight of the sample, expressed in g / cm 3 The porosity is calculated by dividing by the polymer density in mm, dividing by the thickness of the sample in micrometers, multiplying by 100, and subtracting the resulting number from 100, i.e., % porosity=100-[basis weight / (density x thickness) x 100].
[0186] As reported herein, fiber diameter is determined as follows: Scanning electron microscope (SEM) images were taken of each layer of the nanofiber mat sample (e.g., at 20,000, 40,000, or 60,000 times magnification). The diameters of at least 10 clearly identifiable nanofibers are measured and recorded from each SEM image. Irregularities (i.e., nanofiber clumps, polymer droplets, nanofiber crossings, etc.) were not included in the fiber diameter determination.
[0187] As reported herein, nanofiber mat thickness was measured according to ASTM procedure 01777-96, "Standard Test Methods for Thickness of Textile Materials," and is reported in nanometers (nm) or micrometers (μm).
[0188] As reported herein, maximum pore size is determined by the bubble point test defined in ASTM Designation F316-03, "Standard Test Methods for Pore Size Characteristic of Membrane Filters by Bubble Point and Mean Flow Pore Test," reapproved in 2011, and is reported in nanometers (nm).
[0189] As reported herein, bacterial log reduction values (LRVs) are determined according to the standard test method ASTM F838-83, "Standardized Test Method for Determining Bacterial Retention of Membrane FIlers Utilized For Liquid Filtration."
[0190] Unless otherwise noted, all BPs are measured using Galwick® (Porous Materials Incorporated, Ithaca, NY) as the wetting fluid. EXAMPLES
[0191] [Example 1]
[0192] A study was conducted to upgrade the as-spun electrospun nanofiber mat (starting material) to an autoclave sterilizable version using a unique combination of selected qualities from structure, materials, and process.
[0193] Four nanofiber mats were tested, each using a method of electrospinning a polymer solution onto a nonwoven substrate from a spinning electrode (i.e., using a production-scale electrospinning apparatus). Properties of the mats were reported immediately after production without any modification (referred to herein as "as-spun" characterization).
[0194] Table 2 describes the four nanofiber mats and their associated properties. All selected membranes had fiber diameters close to 100 nm for at least one layer of the filter mat such that the filtration media showed complete retention of Blevinsimonas diminuta by size-based separation measured according to ASTM F838-83. All membranes also showed porosity in the range of 85-95%, Galwick® bubble points of at least 15 psi (psig) (considered adequate for complete retention), and liquid permeabilities of greater than 3000 LMH / psi. The maximum pore size of the nanofiber mats is determined by the bubble point test defined in ASTM specification F316-03 using Galwick® as the wetting fluid.
[0195] [Table 2]
[0196] Nanofiber mat types (listed in Table 2) were classified as either "without heat treatment" (see Figure 1, left panel) or "with heat treatment" (see Figure 1, right panel). The heat treatment step involved heating the nanofiber mat rolls in a non-oxidizing environment (e.g., in an anaerobic / inert atmosphere oven) at 208°C for up to 12 hours.
[0197] Prior to autoclaving (or heat and autoclaving), all nanofibrous membranes listed in Table 2 were subjected to an additional wet-dry step, including wetting in water or isopropyl-water solution and drying at 80° C. for 12 hours. Typically, filtration devices (e.g., industrially applied filtration devices) undergo a wet-dry process during integrity testing before reaching the customer's site (sterilized before application). Thus, including such a step ensured that all possible effects of drying effects were accounted for.
[0198] Autoclaving was carried out under aggressive conditions including one or more cycles of heating at 135° C. for 60 minutes followed by a 15 minute dry period. In general, such autoclaving parameters exceed commercially practiced sterilization procedures, which are typically carried out at 126° C.
[0199] <Result>
[0200] This sterilization process resulted in a significant (and expected) decrease in water permeability across all untreated mat types (Figure 1, left panel, compare white and cross-hatched). In particular, polymers, when used to produce nanofibers, undergo molecular scission during the polymer dissolution step due to the use of strong solvents and the high temperatures required by the electrospinning process (80°C, 6 hours). The electrospinning process itself may contribute to molecular chain degradation due to electrostatic forces. The intrinsic viscosity of the nanofiber polymer is significantly lower than that of the native polymer, indicating a detrimental effect of the solvent and electrospinning process on fiber strength. Further degradation occurs in autoclaves under high heat and humidity environments. This is similar to a phenomenon commonly referred to as hydrolytic instability (i.e., the lack of resistance of a cured polymeric material to reverting to a semi-solid or liquid form when exposed to high humidity and temperature).
[0201] In contrast, most nanofiber mats that underwent heat treatment prior to autoclaving showed significantly smaller decreases in water permeability, with the notable exception of heat-treated asymmetric versus symmetric nanofiber mats of nylon-66, which actually showed improved water permeability (see Figure 1, right panel, especially "Asymmetric-N66").
[0202] Solid-state polymerization can occur in condensation polymers such as nylon, where solid prepolymers (and dried monomers) undergo step-growth chemistry with end group functionality to achieve higher molecular weight. Without wishing to be bound by any particular theory, heat treatment can be used to increase molecular weight using solid-state condensation. Solid prepolymer crystals can be grown under inert gas (i.e., non-oxidizing environment) at temperatures above their melting point (Tm ) reacts at lower temperatures, converting the monomer single crystals into highly oriented polycrystalline polymer aggregates. The increase in polymer molecular weight due to heat treatment was confirmed by zero shear melt viscosity data, which is known to correlate with the average molecular weight of the polymer material. Additionally, the heat treatment process was found to improve polymer crystallinity, as evidenced by differential scanning calorimetry (DSC) thermograms. Both molecular weight and crystallinity affect the strength of the nanofiber mat. It should be noted that the "wettability" of the nanofiber mat before and after heat treatment did not change.
[0203] Such data suggest that changes in the mechanical properties of the nanofiber mats are responsible for the observed robustness.
[0204] [Example 2]
[0205] To understand the significance of the combination of architecture, polymeric material, and process (asymmetric vs. symmetric, N66, heat treatment, etc.) and their relative contribution in mitigating permeation loss, the following analysis was performed. Table 3 describes the layout of the experimental design, categorized first by “process”, then by “material”, and then by “architecture”. Then, the impact of each factor, and the combination of factors (as shown in Figure 1) on the water permeability loss was evaluated. Notably, by instituting this kind of sorting order, the nanofiber mats were automatically arranged in ascending order by the observed water permeability loss, showing the differences in the relative contribution of these parameters (see the “Output” column in Table 3).
[0206] [Table 3]
[0207] A main effects plot (see Figure 2) was used to compare the mean response values at each process parameter with the relative strength of the influence of the various factors in the experiment. Briefly, when the columns are horizontal (parallel to the x-axis), there are no main effects. Each level of the factor affects the response in the same way, and the response mean % permeability loss is the same across all factor levels. However, when the columns are not horizontal, the factor affects the outcome (i.e., permeability). Different levels of the factor affect the response differently. Furthermore, the steeper the slope of the column, the larger the magnitude of the main effect. Figure 2 clearly shows that in terms of influence, there is an apparent order of process > material > structure. Additional analysis confirmed that all three effects have a statistically significant impact on permeability loss.
[0208] [Example 3]
[0209] The morphology of asymmetric nanofiber mats was also studied by scanning electron microscopy (SEM), which subjected the mats to at least three rounds of autoclaving (AC3x). Mats containing nylon-6 (N6) and treated without heat treatment showed the most dramatic structural changes. The SEM micrographs in Figure 3 show that the fibers, which were linearly oriented before sterilization, became wavy and appeared to contain more fusion at fiber intersections (see upper panel). On the other hand, nylon-66 (N66) nanofibers subjected to heat treatment did not show significant morphological differences before and after sterilization (see lower panel), consistent with the observed robustness of the mats, as evidenced by minimal (if any) loss in water permeability.
[0210] [Example 4]
[0211] The heat treated asymmetric N66 nanofiber mats with significant improvement in water permeability were subjected to more than three cycles of autoclave sterilization. When all three factors (heat treated nylon-66 asymmetric) were performed, the nanofiber mats were robust enough to withstand up to 12 autoclave cycles and showed no significant negative impact on water permeability (see FIG. 4). In addition to the observed improvement in water permeability, the bubble point (or BP, using Galwick® as the wetting fluid), a measure of the retention properties of the mats, increases after the first three cycles of autoclave sterilization and remains constant for subsequent autoclave cycles. This increase in BP provides further assurance to the mat retention behavior.
[0212] Furthermore, multiple autoclave cycles appeared to have little effect on the nanofiber morphology in the best performing mat (i.e., heat treated asymmetric nylon-66 mat), even after 12 autoclave cycles (12 x AC) (see Figure 5). This data suggests that the heat treated asymmetric N66 mat is robust in the face of moist heat sterilization. Such nanofiber mats show no degradation to moderate improvement in water permeability after as many as 12 autoclave cycles.
[0213] Incorporation by Reference
[0214] All publications, patents, and patent applications mentioned herein are incorporated by reference in their entirety as if each individual publication, patent, or patent application was specifically and individually indicated to be incorporated by reference. In the case of conflicts, the present application, including any definitions herein, will control.
[0215] Equivalent
[0216] Those skilled in the art will recognize, or be able to ascertain using no more than routine experimentation, many equivalents to the specific embodiments described herein which are intended to be encompassed by the claims appended hereto.
Claims
1. A method for sterilizing a liquid filtration medium, This includes sterilizing a heat-treated liquid filtration medium using moist heat sterilization, The liquid filtration medium comprises a nanofiber mat produced by electrospinning a polymer solution or melt containing at least one of nylon-6, nylon-6,6, and any mixture thereof, wherein the heat treatment brings the nanofiber mat to the glass transition temperature (T) of the nanofibers. g ) or higher, but the melting temperature (T) of the nanofiber m A method comprising heating to a temperature that is less than or equal to T m and 1°C to 80°C lower than T m for at least 1 hour.
2. The method according to claim 1, wherein the liquid filtration medium resists post-sterilization changes in liquid permeability compared to a corresponding filtration medium that has not been heated to the temperature before sterilization.
3. The method according to claim 1, wherein the liquid filtration medium exhibits a bubble point pressure of 34.45 kPa to 1033.5 kPa.
4. The method according to claim 1, wherein the liquid filtration medium exhibits a logarithmic decline value (LRV) of at least 1 of Brevundimonas diminuta as measured according to ASTM F838-83.
5. The method according to claim 1, wherein the liquid filtration medium has a porosity of 80% to 95%.
6. The method according to claim 1, wherein the liquid filtration medium exhibits a liquid permeability of more than 145.14 LMH / kPa.
7. The method according to claim 1, wherein the liquid filtration medium exhibits a decrease of 40% or less in liquid permeability after sterilization.
8. The method according to claim 1, wherein the nanofiber has a fiber diameter of 5 nm to 1000 nm.
9. The method according to claim 1, wherein the nanofiber mat includes either 1) a symmetric nanofiber mat, or 2) an asymmetric nanofiber mat having a fiber diameter that varies over the thickness of the nanofiber mat such that the average fiber diameter of one layer of the nanofiber mat is different from that of the other layers of the nanofiber mat.
10. The method according to claim 9, wherein the average fiber diameter changes continuously from one layer to the other of the asymmetric nanofiber mat.
11. The method according to claim 9, wherein the ratio of the average fiber diameter of one layer of the asymmetric nanofiber mat to that of the other layer is at least 1.
15.
12. The method according to claim 9, wherein the average fiber diameter is 5 nm to 1000 nm for at least one layer of the asymmetric nanofiber mat.
13. The method according to claim 1, wherein the polymer is nylon-6,6.
14. The method according to claim 1, wherein the heat treatment comprises heating the nanofiber mat to 56°C below T m.
15. The method according to claim 1, wherein the heat treatment comprises heating the nanofiber mat to 75°C below T m.
16. The method according to claim 1, wherein the heat treatment comprises heating the nanofiber mat to 100°C to 200°C above Tg.
17. The method according to claim 1, wherein the heat treatment comprises heating the nanofiber mat in a non-oxidizing environment.
18. The method according to claim 1, wherein the heat treatment comprises heating the nanofiber mat for at least 1 hour to at least 24 hours.
19. The method according to claim 1, wherein the use of moist heat sterilization includes autoclaving.
20. The method according to claim 1, wherein the use of moist heat sterilization includes steam treatment.
21. The method according to claim 1, wherein the use of moist heat sterilization includes tinderization.
22. A method for processing a liquid filtration medium, This includes subjecting a heat-treated liquid filtration medium to a wetting / drying process, The liquid filtration medium comprises a nanofiber mat produced by electrospinning a polymer solution or melt containing at least one of nylon-6, nylon-6,6, and any mixture thereof, and the heat treatment comprises heating the nanofiber mat for at least one hour at a temperature above the glass transition temperature (T g) of the nanofibers but below the melting temperature (T m) of the nanofibers, and 1°C to 80°C lower than T m.
23. The method according to claim 22, wherein the wetting / drying process includes an integrity test.
24. The method according to claim 22, further comprising sterilizing the liquid filtration medium after the wetting / drying process.
25. The method according to claim 24, wherein the liquid filtration medium resists post-sterilization changes in liquid permeability compared to a corresponding filtration medium that has not been heated to the temperature before sterilization.
26. The method according to claim 24, wherein the liquid filtration medium exhibits a decrease of 40% or less in liquid permeability after sterilization.
27. The method according to claim 22, wherein the liquid filtration medium exhibits a bubble point pressure of 34.45 kPa to 1033.5 kPa.
28. The method according to claim 22, wherein the liquid filtration medium exhibits a logarithmic decline value (LRV) of at least 1 for Brevundimonas diminuta as measured according to ASTM F838-83.
29. The method according to claim 22, wherein the liquid filtration medium has a porosity of 80% to 95%.
30. The method according to claim 22, wherein the liquid filtration medium exhibits a liquid permeability of more than 145.14 LMH / kPa.
31. The method according to claim 22, wherein the nanofiber has a fiber diameter of 5 nm to 1000 nm.
32. The method according to claim 22, wherein the nanofiber mat includes either 1) a symmetric nanofiber mat, or 2) an asymmetric nanofiber mat having a fiber diameter that varies over the thickness of the nanofiber mat such that the average fiber diameter of one layer of the nanofiber mat is different from that of the other layers of the nanofiber mat.
33. The method according to claim 32, wherein the average fiber diameter changes continuously from one layer to the other of the asymmetric nanofiber mat.
34. The method according to claim 32, wherein the ratio of the average fiber diameter of one layer of the asymmetric nanofiber mat to that of the other layer is at least 1.
15.
35. The method according to claim 32, wherein the average fiber diameter is 5 nm to 1000 nm for at least one layer of the asymmetric nanofiber mat.
36. The method according to claim 22, wherein the polymer is nylon-6,6.
37. The method according to claim 22, wherein the heat treatment comprises heating the nanofiber mat to 56°C below Tm.
38. The method according to claim 22, wherein the heat treatment comprises heating the nanofiber mat to 75°C below T m.
39. The method according to claim 22, wherein the heat treatment comprises heating the nanofiber mat to 100°C to 200°C above Tg.
40. The method according to claim 22, wherein the heat treatment comprises heating the nanofiber mat in a non-oxidizing environment.
41. The method according to claim 22, wherein the heat treatment comprises heating the nanofiber mat for at least 1 hour to at least 24 hours.